2010
DOI: 10.3748/wjg.v16.i23.2918
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave velocity is a useful marker for managing nonalcoholic steatohepatitis

Abstract: The clinical implementation of ARFI provides noninvasive repeated evaluations of liver stiffness at an arbitrary position, which has the potential to shed new light on NASH management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 24 publications
1
73
0
Order By: Relevance
“…Serum HA levels were associated with a diagnosis of NASH in a small NAFLD sample, owing mainly to elevated HA levels in patients with advanced steatosis (93). HA levels measured by latex agglutination (normal <50 ng/mL) were associated with shear wave velocity, another technique used to assess liver fibrosis, in a small sample of 23 NASH patients (94). Ethyl-eicosapentanoic acid had no effect on the degree of fibrosis or on the HA levels in a double-blind, randomized, placebo-controlled trial using 243 NAFLD/NASH patients (95).…”
Section: Hyaluronic Acid In Autoimmune Hepatitismentioning
confidence: 95%
“…Serum HA levels were associated with a diagnosis of NASH in a small NAFLD sample, owing mainly to elevated HA levels in patients with advanced steatosis (93). HA levels measured by latex agglutination (normal <50 ng/mL) were associated with shear wave velocity, another technique used to assess liver fibrosis, in a small sample of 23 NASH patients (94). Ethyl-eicosapentanoic acid had no effect on the degree of fibrosis or on the HA levels in a double-blind, randomized, placebo-controlled trial using 243 NAFLD/NASH patients (95).…”
Section: Hyaluronic Acid In Autoimmune Hepatitismentioning
confidence: 95%
“…To the best of our knowledge, performance of ARFI in detecting fibrosis has been investigated in study of healthy adult volunteers [20] and in patients affected by different hepatopathies [7][8][9][10][11][12][13][14][15]. Average SWV has been found correlating with serum markers of fibrosis (i.e.…”
Section: Sign Of Pancreatic/liver Involvementmentioning
confidence: 99%
“…Theoretically, the stiffer is the tissue, the faster the shear wave will be propagated [7]. Quantitative in vivo measurements of parenchymal stiffness and shear wave velocities (SWV) have been obtained in chronic hepatopathies including viral hepatitis [7][8][9][10][11][12] and nonalcoholic fatty liver disease [13,14]. We recently reported preliminary data on SWV in a sample of 40 young patients with cystic fibrosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…ARFI has been suggested for patients with a high BMI [51] , which can affect the accuracy of liver stiffness measurements. AUROCs reported with ARFI for the diagnosis of F3-F4 in NAFLD ranged from 0.74 to 0.97 [43,50,52,53] . One study evaluating liver stiffness in 54 patients with biopsy-confirmed NAFLD and 10 healthy volunteers found a significant correlation between ARFI and TE [43] .…”
Section: Acoustic Radiation Force Impulsementioning
confidence: 99%